Queering Interventions: Improving pre-service teachers’ knowledge and awareness of LGBTQI+ inclusive practice - McKenzie, Bri; Chen, Julian; Andreassen, Kimberley; Smith, Cindy (2024)
LGBTQIA+ is an acronym that stands for ‘lesbian, gay, bisexual, transgender, intersex, queer/questioning, asexual and other diverse sexualities and genders’. In Australia, LGBTQIA+ people still experience extensive discrimination within the education system, a recent report highlighting that most Australian LGBT students felt unsafe in secondary school. LGBTQIA+ youth in Australia have significantly higher rates of anxiety, mental health conditions and suicide attempts when compared to the general population. At the same time, pre-service teacher training in Australia is not consistent in providing information and support to prospective educators in LGBTQIA+ inclusive practice and curricula development. This paper explores the initial results of a multi-phase, ongoing project designed to assist pre-service teachers in developing their awareness and understanding of LGBTQIA+ inclusive practice. Utilizing Participatory Action Research (PAR), co-creation and the Design Justice Principles (DJP), the research group sought stakeholder feedback from both pre-service teachers, LGBTQIA+ identified educators and LGBTQIA+ allies to design and deliver LGBTQIA+ inclusive training and resources. Data was collected from pre-service teacher’s survey responses to a professional learning workshop on LGBTQIA+ inclusive practice, revealing high value in understanding inclusive language and discussions of gender diversity and desire for earlier inclusion of these topics in teaching degrees. This was followed by a co-creation phase, resulting in the development of a queering curriculum resource site, followed by a focus group with lived experience stakeholders. This latter phase of the project drew upon insider perspectives to help refine the co-designed resources to make them more intersectional, inclusive, and relevant. The resulting analysis highlights the link between our research and the DJP, while emphasizing the importance of ‘listening to the voices from within’ by establishing meaningful, ongoing stakeholder engagement in the development and delivery of inclusive education resources and materials.